PRIME performance under impulsive noise environments - Matanza Domingo, Javier (Sin editorial (Pekín, China), 2012)
The presented paper addresses the problem of impulsive noise interferences in Power Line Communication (PLC) systems. In order to provide a realistic scenario, a popular narrow band PLC solution has been chosen: PRIME. System’s performance is evaluated under different impulsive noise environments. Simulations show how, even when the high-powerful time impulses hits a few signal samples, the noise energy corrupts most of the symbol in the OFDM spectrum. This affects directly the performance in terms of BER vs. SNR despite using the most robust communication mode in PRIME. Additionally, two common techniques are proposed to increase the performance under this kind of disturbances. The paper shows detailed figures with the improvement and a discussion of their usability.
Capítulos en libros
Keywords: Instituto de Investigación Tecnológica (IIT)